Can multi-cropping affect soil microbial stoichiometry and functional diversity, decreasing potential soil-borne pathogens? A study on European organic vegetable cropping systems - Trinchera, Alessandra; Migliore, Melania; Warren Raffa, Dylan; Ommeslag, Sarah; Debode, Jane; Shanmugam, Sindhuja; Dane, Sandra; Babry, Joran; Kivijarvi, Pirjo; Kristensen, Hanne Lakkemborg; Lepse, Liga; Salo, Tapio; et al. (Frontiers in Plant Science, 2022)
Since plant diversity and soil microbial communities are the main drivers of biogeochemical C and nutrient cycling, crop diversification in spatial and temporal patterns can optimize the synchronization of nutrients plant demand and availability in soil. Thus, the introduction of multi-cropping in organic vegetable production may represent a key strategy to ensure an efficient complementation mediated by soil microbiota, including beneficial mycorrhizal fungi. The present study shows the effect of the introduction of multi-cropping in five European organic vegetable cropping systems (South-West: Italy; North-West: Denmark Belgium; North-East: Finland and Latvia) on: (i) soil physico-chemical parameters; (ii) soil microbial biomass abundance and stoichiometry; (iii) crop root mycorrhization; (iv) bacterial and fungal diversity and composition in crop rhizosphere; (v) relative abundance of selected fungal pathogens species. In each site, three cropping systems were considered: 1) crop 1 – monocropping; 2) crop 2 - monocropping; 3) crop 1 - crop 2 - intercropping or strip cropping. In each plot, the following measurements were performed: soil bulk density; pH; total organic C; total N; available P; organic C and P soluble in hot water; C-N-P microbial biomass content and their relative ratios; mycorrhizal colonization intensity of crop roots; bacteria and fungi diversity indexes; bacteria and fungi community composition (phyla relative abundance); relative abundance of Fusarium spp. and Olpidium Brassicae L. Results showed that, just before harvest, multi-cropping can increase soil microbial biomass amount and shape microbial community towards predominance of some bacteria or fungi phyla, in function of soil nutrient availability. We mainly observed a selection effect of crop type on rhizosphere microbiota. Particularly, Bacteroidetes and Mortierellomycota abundances in rhizosphere soil resulted suitable ecological indicators of the positive effect of plant diversity in field, the first ones attesting an improved C and P cycles in soil and the second ones a reduced pressure by soil pathogens. Plant diversity also increased the root mycorrhizal colonization between the intercropped crops that, when properly selected, can also reduce the abundance of potential soil-borne pathogens, with positive effect on crop productivity on long term.